Treatment of Achilles insertional tendinopathy: our surgical procedure and medium-term results - Lugani, Giovanni; Santandrea, Alessandro; Mercurio, Domenico; Puddu, Leonardo; Silvestri, Jessica; Cortese, Fabrizio (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Achilles insertional tendinopathy (AIT) is a common injury and its pathogenesis is still not entirely clear. It manifests with worsening pain and functional limitations. When conservative treatment fails, surgical treatment is indicated. The purpose of our research is to evaluate the outcome after one year in patients affected by AIT (calcific and non-calcific AIT) who were treated at our centre. Methods: Between 2014 and 2021, 42 patients suffering from AIT – a total of 47 feet – underwent surgery at our centre. The patients filled in the VISA-A and AOFAS questionnaires at the pre-operative consultation and at the clinical check-up after one year of follow up. Results: Of the 47 feet treated, 28 were calcific AITs treated by medial access and tendon reinsertion using a knotless double suture anchor system (Achilles Suture Bridge™) and 19 were non-calcific tendinopathies treated using a lateral paratendinous approach. The one-year clinical results show an increase in VISA-A scores of 48.6 and AOFAS scores of 44.1 and the absence of complications. Only one patient reported a recurrence of certain symptoms and none of the patients were hospitalized for recurrence. Conclusions: The literature is unable to establish a gold standard of treatment for AIT. The method we have used has shown excellent short- and medium-term results without any complications. Further studies are needed to prove its effectiveness in the long term.